(untitled) (Journal of actual problems of jurisprudence, 2018)
Author of the article provides for the right of international criminal extradition. Part of the extradition of the criminal law, including those who consider it as a penal institution. At the same time, the author of the article went to look out the extradition problems reviews of foreign countries. Key words: law, extradition, the fight against crime, responsibility.